EFEKTIVITAS TUGAS PEMBANTUAN (hMEDEBEWIND) PADA DINAS PERTANIAN TANAMAN PANGAN KABUPATEN PELALAWAN (STUDI KASUS PADA PROGRAM PERTANIAN) - Yudistira Yola Saputra; Harapan Tua R.F.S (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Based the task of Agriculture Department Program, in the five years, the Document showed that the activities and budgets have ups and downs in every year. Formulation of the problemin this research is how “The Effectiveness of co-Administration at the Dapartment of Agriculture Crops in Pelalawan District” with the aim of research to find out “The Effectiveness of co-Administration at the Dapartment of Agriculture Crops in Pelalawan District, and determine the factors that influence the Effectivieness of co-Adminstration at the Department of Agriculture crops in Pelalawan District”The method in this research used is descriptive qualitative, the analysis that seeks to provide a detailed description based on the facts found in the field of the strategi of co-Administration, particularly the co-Administration of Agriculture Program. Data use in this study consisted of primary data Source Approach, Proccess Approach, Goal Approach. Data collection techniques including observation, interviews, and a review of documentation involved four people consisting of a head of Department, a secretan a head of the Program and a employee Department of Agriculture Crops.Keyword : Effectiveness, co-Administration, Agriculture Progra